Choosing the Proper Interface for Positive Airway Pressure Therapy in Subjects With Acute Respiratory Failure - BaHammam, Ahmed S; Singh, Tripat Deep; Gupta, Ravi; Pandi-Perumal, Seithikurippu R (Respiratory care, 2018)
Noninvasive ventilation is an effective treatment for a significant proportion of patients with acute respiratory failure. The success of noninvasive ventilation, however, depends on several factors, a major one being the selection of the proper interface. The choice and application of the interface in patients with acute respiratory failure is a considerable challenge for any treatment team. This review discusses the different types of interfaces that can be used in patients with acute respiratory failure, the differences between nasal, oro-nasal, and total face masks and the helmet, as well as the effect of interface type on treatment success and upper airway patency, mask fitting, problems related to the interface, and the relationship between ventilator type and interface choice.